2021
DOI: 10.3390/nu13051402
|View full text |Cite
|
Sign up to set email alerts
|

DeltaF508 CFTR Hetero- and Homozygous Paediatric Patients with Cystic Fibrosis Do Not Differ with Regard to Nutritional Status

Abstract: The purpose of this study was to compare the nutritional status between deltaF508 CFTR hetero- and homozygous paediatric patients with cystic fibrosis. We assessed the percentage profiles of fatty acids measured in erythrocyte membranes and the serum levels of vitamins A, D3, E and K1 in the studied groups. We also measured the weights and heights and calculated the body mass indexes (BMIs). The studied groups consisted of 34 heterozygous and 30 homozygous patients. No statistically significant differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In another study, Medza et al compared people with CF who were either heterozygous or homozygous for Phe508del [ 46 ]. They demonstrated that the serum vitamins and erythrocyte membrane fatty acid profiles were the same in both groups, except for heptadecanoic acid.…”
Section: Effect Of Genotypementioning
confidence: 99%
“…In another study, Medza et al compared people with CF who were either heterozygous or homozygous for Phe508del [ 46 ]. They demonstrated that the serum vitamins and erythrocyte membrane fatty acid profiles were the same in both groups, except for heptadecanoic acid.…”
Section: Effect Of Genotypementioning
confidence: 99%
“…This outcome is contrary to a comparative study between compound heterozygous and homozygous ∆F508 CFTR pediatric patients. It was observed that the nutritional parameters studied (fat-soluble vitamins, fatty acid profile, weight, height, and BMI) did not differ [24]. Even though genotype did not predict individual nutritional phenotype, based on the molecular phenotypic complexity of CFTR mutants and their susceptibility to pharmacotherapy, mutations may impose combinatorial defects in CFTR channel biology that must be considered [25].…”
Section: Clinical Statusmentioning
confidence: 98%
“…Individuals homozygous for F508del typically present with earlier and more severe respiratory complications and have earlier mortality ( Johansen et al, 1991 ; De Braekeleer et al, 1997 a; Mackenzie et al, 2014 ; Keogh et al, 2018 ). Most F508del homozygotes have exocrine pancreatic insufficiency but the effect of this genotype on weight and body mass index is controversial ( Lanng et al, 1991 ; Santos and Steemburgo, 2015 ; Leung et al, 2020 ; Medza et al, 2021 ). Homozygotes for F508del also have impaired glucose tolerance and a higher risk of cystic fibrosis-related diabetes (CFRD) ( Hamdi et al, 1993 ; Street et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%